The Effectiveness of the Use of Android-Based Andro Poster Learning Media on the Numeracy Skills of Seventh Grade Junior High School Students - Bima Pambudi; Roemintoyo Roemintoyo; Deny Tri Ardianto (PAEDAGOGIA, 2025)
Numeracy skills or numeracy literacy is a basic competency that is important for junior high school students to master in facing the challenges of the 21st century and the Industrial 5.0 era. However, PISA 2023 data shows that Indonesian students are still ranked low in math skills, reflecting students' weak numeracy skills. This study aims to test the effectiveness of Android-based Andro Poster learning media in improving the numeracy skills of grade VII junior high school students. The research uses a pre-experimental quantitative method with a One Group Pretest-Posttest Design. The research sample consisted of 30 students in grades VII-9 of junior high school who were selected through purposive sampling techniques. The research instrument was in the form of a numeracy multiple-choice test of 10 items, which was developed based on indicators of numeracy ability in the submaterial of algebraic forms. Data were obtained through pretest and posttest, then analyzed using paired sample t-tests and effect sizes (Cohen's d). The results showed that the average posttest score (72.87) increased significantly compared to the pretest (60.97), with a p value of < 0.001. The correlation between pretest and posttest of 0.865 shows a very strong relationship. In addition, Cohen's d value of -2.905 indicates a very large measure of effect on students' improved numeracy skills. Andro's Poster Media successfully presents algebra material visually, contextually, and interactively, so that it can increase students' motivation to learn and understand. This study concludes that the use of Android-based learning media such as Poster Andro is an effective and innovative strategy in improving the numeracy skills of junior high school students. This finding is expected to be a practical solution in mathematics learning as well as contribute to the development of digital media that is adaptive to the learning needs of students in the digital era.